Structural Accounting Support Service for Construction Companies in Malaysia - A Qualitative Pilot Test - Abdul Rahman, Che Azizah; Abdullah, Norhayati; Abdul Kadir, mohd rizuan (2013)
The objective of the qualitative study is to gauge the awareness of contractors of the Small Construction Companies (SCCs) on the Structural Accounting Support System (SASS). This paper looks at a pilot test before a qualitative study is to be conducted. The sample of this study is obtained from the population of SCCs in Malaysia under the category of grade G1 and G2 contractors, as defined by the Construction Industry Development Of Board (CIDB), Malaysia. A total of four pilot tests were conducted among the SCC in Terengganu and Kelantan, Malaysia. The designed interview questions from a preliminary study and review of literature demanded modification after the pilot study. As such, these questions were readjusted and realigned to meet the objectives of the study. Most importantly, the finding addresses the design of the questions to meet two different situations. One situation is in preparing companies' accounts by the internal staff of the SCCs. The other situation is when the SCCs outsource the accounts preparation. This pilot study is crucial for the subsequent phases of the development process of structural accounting support service for the SCCs in Malaysia.